Battery economy: Past, present and future. (2022) - Kandeeban, R.; Saminathan, K.; Manojkumar, K.; Dilsha, C.G.; Krishnaraj, S.
Abstract: Batteries are researched and commercialized because it can be potential replacement of the rapidly depleting fossil fuels. This arises the question about the future of current employees in fossil fuels sector, is the current innovations can replace fossil fuel and whether the current battery companies can accommodate the demand that will be created once fossil fuels completely depleted. In this work, statistics of employees, viable changes in secondary batteries made and the demand, turnover of batteries and its manufacturing companies were plotted and discussed. Based on that although the current trends and collaborations between nations were effective and rapid then before still it would not be adequate to replace fossil fuels before the time runs out. The nations have to aid more regarding batteries.